GROWTH RATE, COVER, AND SURVIVAL RATE (Enhalus acoroides) TRANSPLANTED IN MONOSPECIES AND MULTISPECIES - Ilham Antariksa Tasabaramo; Mujizat Kawaroe; Rohani Ambo Rappe (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2015)
One of seagrass dominant species found in Indonesia is Enhalus acoroides. This species can form single seagrass bed vegetation (monospecies vegetation) and mixed with others species (multispecies vegetation). Seagrass composition in coastal areas can be affected by surrounding associated species such as herbivorous fish and invertebrates. Human activities, especially in coastal communities, can negatively influence seagrass beds. Therefore, it is needed an effort to rehabilitate the affected seagrass. Transplantation technic is one effort for rehabilitation. The purposes of the research were to analyze growth rate, percent cover, and survival rates of seagrass E. acoroides transplanted as monospecies and multispecies. This research used a monospecies of E. acoroides and multispecies (2, 4, and 5 species) that combined to others species such as T. hemprichii, C. rotundata, H. ovalis, H. uninervis, and S. isoetifolium. Research results showed that the highest average growth rate of transplanted E. acoroides was found in monospecies treatment with 0.29 cm/day. The highest average cover changing was found on two combined species i.e., E. acoroides and C. rotundata, as high as 0.10% per day. The highest survival rates were found in 2 combined treatment i.e., E. acoroides and H. ovalis, and 5 combined species such as E. acoroides, S. isoetifolium, C. rotundata, H. uninervis dan H. ovalis with value 100 percent, respectively. Keywords: Enhalus acoroides, cover, growth, survival rates, seagrass, transplantation